Liver‐Targeted Angiotensin Converting Enzyme 2 Therapy Inhibits Chronic Biliary Fibrosis in Multiple Drug‐Resistant Gene 2‐Knockout Mice. Issue 12 (10th October 2019) - Rajapaksha, Indu G.; Gunarathne, Lakmie S.; Asadi, Khashayar; Cunningham, Sharon C.; Sharland, Alexandra; Alexander, Ian E.; Angus, Peter W.; Herath, Chandana B.
Abstract : There is a large unmet need for effective therapies for cholestatic disorders, including primary sclerosing cholangitis (PSC), a disease that commonly results in liver failure. Angiotensin (Ang) II of the renin Ang system (RAS) is a potent profibrotic peptide, and Ang converting enzyme 2 (ACE2) of the alternate RAS breaks down Ang II to antifibrotic peptide Ang‐(1‐7). In the present study, we investigated long‐term effects of ACE2 delivered by an adeno‐associated viral vector and short‐term effects of Ang‐(1‐7) peptide in multiple drug‐resistant gene 2‐knockout (Mdr2‐KO) mice. These mice develop progressive biliary fibrosis with pathologic features closely resembling those observed in PSC. A single intraperitoneal injection of ACE2 therapy markedly reduced liver injury ( P < 0.05) and biliary fibrosis ( P < 0.01) at both established (3‐6 months of age) and advanced (7‐9 months of age) disease compared to control vector‐injected Mdr2‐KO mice. This was accompanied by increased hepatic Ang‐(1‐7) levels ( P < 0.05) with concomitant reduction in hepatic Ang II levels ( P < 0.05) compared to controls. Moreover, Ang‐(1‐7) peptide infusion improved liver injury ( P < 0.05) and biliary fibrosis ( P < 0.0001) compared to saline‐infused disease controls. The therapeutic effects of both ACE2 therapy and Ang‐(1‐7) infusion were associated with significant ( P < 0.01) reduction in hepatic stellate cell (HSC) activation and collagen expression. While ACE2 therapy prevented the loss of epithelial characteristics of hepatocytes and/or cholangiocytes in vivo, Ang‐(1‐7) prevented transdifferentiation of human cholangiocytes (H69 cells) into the collagen‐secreting myofibroblastic phenotype in vitro . We showed that an increased ratio of hepatic Ang‐(1‐7) to Ang II levels by ACE2 therapy results in the inhibition of HSC activation and biliary fibrosis. Conclusion: ACE2 therapy has the potential to treat patients with biliary diseases, such as PSC. Abstract :